Welcome to dystopia : forty-five visions of what lies ahead - Van Gelder, Gordon (OR Books LLC, 2019)
"In this diverse and vigorous mix of stories by newcomers and luminaries, writers offer their takes on what life might hold for us in the next few years. The resulting visions of war, oppression, and daily struggle are sometimes humorous, sometimes terrifying (and occasionally both), but always thought-provoking." --